Online surveys as an element feedback in building cloud educational environment - Yu. V. Gritsuk; O. V. Gritsuk (Academy of Cognitive and Natural Sciences, 2014)
The aim of this study is an analysis of questionnaires benefits over other means of feedback in learning. Objectives of the study is to determine differences between surveys and tests, review of cloud services to create polls. The object of research is the organization of surveys in the educational process. The subject of research is the use of cloud-based tools for creating surveys in the educational process. The differences in the usage of tests and surveys in the study process is shown. A cloud services to create polls are supposed. The basic directions of the online survey are given.